PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS, DAN RESILIENSI MATEMATIS SISWA SMP MELALUI MODEL ELICITING ACTIVITIES (MEAS) - Rifdah, - (2020)
The goals of this research is to get a picture about the enhancement of critical thinking and mathematical resilience students after learning using Model Eliciting Activities (MEAs). This research conducted in the private junior high school in Central Jakarta class VIII, even semester in the academic year 2018-2019. The method of this research is a quasi experiment. The research sample consisted of one experimental class and one control class selected based on cluster random sampling technique. The material used in this research was build a flat side room. The research instrument consisted of 5 critical thinking ability problems, and 25 statements of mathematical resilience. The results showed that 1) the enhancement of mathematical critical thinking abilities of students who study with Model Eliciting Activities (MEAs) higher than students who study with conventional learning; 2) the enhancement of mathematical critical thinking abilities of students who study with Model Eliciting Activities (MEAs) higher than students who study with conventional learning when reviewed based on KAM (high, medium and low, 3) Achieving the mathematical resilience of students who who study with Model Eliciting Activities (MEAs) higher than students who study with conventional learning reviewed as a whole, 4) there is a correlation between mathematical resilience and critical thinking ability, meaning that there is a significant relationship between mathematical resilience and critical thinking ability. Keywords: Critical Thinking Mathematics Ability, Mathematical Resilience, Model Eliciting Activities (MEAs).